Enhancing Culinary Policies for Halal and Non-Halal Labeling: Protecting Muslim Consumers in Global Jakarta - Pamungkas, Bani; Saraswati; Yusuf, Maulana (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2024)
This study aims to analyze the dynamics of preserving and sharing halal food information for Muslim consumers in multicultural and global contexts. Access to halal food is essential in Muslim-majority regions. However, the rise of multiculturalism and global cosmopolitanism has led to acculturation in native foodways and diversification of culinary products. In Jakarta, a Muslim-majority city with rich multicultural complexity, merging culinary traditions often blur distinctions between halal and non-halal foods.Using qualitative methods, including in-depth interviews with culinary associations and enterprises in Singapore and Malaysia and an intensive literature review, this study identifies key practices and challenges in halal and non-halal labeling. Findings indicate that transparent and honest disclosure of non-halal product information is crucial for supporting enterprises in meeting halal certification standards. These measures protect Muslim consumers, enhance international consumer trust, and foster compliance with global food standards. In the post-pandemic era and Jakarta's transition to a global metropolis after the capital relocation, there is an urgent need to improve culinary literacy initiatives and standardize labeling procedures. These initiatives will strengthen Jakarta’s role as an inclusive and multicultural city, capable of addressing diverse dietary needs. This study, however, is limited in addressing broader policy and regulatory frameworks to ensure compliance across the culinary sector. Future research should explore strategies to overcome these limitations within Jakarta’s complex urban landscape. The findings emphasize the significance of clear labeling and regulatory consistency to promote local businesses, safeguard consumer trust, and support Jakarta’s evolving role in the global market.